Analisis Dampak Sosial Ekonomi Dari Penutupan Lokalisasi Gude Terhadap Eks - Pekerja Seks Komersial Mucikari Dan Masyarakat Terdampak Yang Berdomisili Di KabupatenMadiun - Rismala, Rina; , Drs. Priyono, M.Si (2016)
This research was conducted in Gude Prostitution Complex, Teguhan Village, Jiwan Sub-district, Madiun Regency. Gude that is near to the bus lane of Surabaya-Surakarta can be said as strategic enough because it is a transit place. Nevertheless, due to the policy of the Regional Government of Madiun Regency to close Gude Prostitution Complex, impacts were arisen on the people who work and live in this area. This research aimed at 1) Studying the characteristics of the ex-prostitutes, pipms, and people who got impacts who have domicile in Madiun Regency. 2) Studying the use of severance pay and counseling given by Dinsosnakertrans (Agency of Social, Labor, Transmigration). 3) Studying the social-economic impact on the ex-prostitutes, pimps, and people who got the impacts. The method used is the method of census. Data used in this research are primary and secondary data. Primary data used questionnaire including the characteristics of demography and social-economy. The secondary data obtained are data on the use of land, number of population according to age, gender, educational level, health care, social problems, maps, etc, obtained from Dinsosnakertrans and BPS (Center Bureau of Statistics) Madiun Regency. The result of analysis show that: a) About the ex-prostitutes, most of them are residents of Madiun Regency. The age of the ex-prostitutes are 20-40 years old in which each age group is 58.3%. The duration of the ex-prostitutes' work in Gude is mostly 10 years as much as 41.6%. The ex-prostitutes' marital status is mostly married. The lowest education which is elementary graduation is as much as 75%. Most of the customers are entrepreneurs as much as 58.3%. The amount of children that still must be funded for tuition fee is mostly none because the children had been graduated which is as much as 58.3%. b) About the pimps, most of them are residents of Madiun Regency. The pimps' age which is more than 40 years old is as much as 94.1%. The pimps are mostly married. Their education background is mostly low, only being graduated from elementary school which is as much as 82.3 %. The amount of children that still must be funded for tuition fee is mostly one child which is as much as 58.8%. c) About the people who got the impact are mostly residents of Madiun Regency. Their age which is more than 40 years old is as much as 70%. The people who got the impacts are mostly married. Their educational background is low, only being graduated from elementary school which is as much as 50%. The amount of children that still must be funded for tuition fee is mostly none which is as much as 70%.About the use of severance pay obtained from the Government, the ex-prostitutes who used it for capital is as much as 50%. The pimps using it for capital are as much as 52.9%. The people who got the impacts who also used it for capital is as much as 50%. About the impacts arisen, the ex-prostitutes who work of running a stall is as much as 76.4%. The people who got the impacts who are mostly jobless is as much as 35%.